Ionic liquids to monitor the nano-structuration and the surface functionalization of material electrodes: a proof of concept applied to cobalt oxyhydroxide. Issue 6 (26th April 2019) - Olchowka, Jacob; Tailliez, Tiphaine; Bourgeois, Lydie; Dourges, Marie Anne; Guerlou-Demourgues, Liliane
Abstract : This paper reports on an innovative and efficient approach based on the use of ionic liquids to govern the nano-structuration of HCoO2, in order to optimize the porosity and enhance the ionic diffusion through the electrode materials. Abstract : This paper reports on an innovative and efficient approach based on the use of ionic liquids to govern the nano-structuration of HCoO2, in order to optimize the porosity and enhance the ionic diffusion through the electrode materials. In this work, we show that (1-pentyl-3-methyl-imidazolium bromide (PMIMBr) and 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4 )) ionic liquids (ILs) used as templates during the synthesis orientate the nanoparticle aggregation which leads to increase of the porosity and the average pore size of the electrode material. It is also demonstrated that the ILs are strongly bonded to the HCoO2 surface, leading to surface functionalized HCoO2 materials, also called nanohybrids. This surface tailoring stabilizes the material upon cycling and shifts the oxidation potential linked to the Co(iii )/Co(iv ) redox couple to lower voltage in an alkaline 5 M KOH electrolyte. The surface and porosity optimizations facilitate the ionic diffusion through the material, improve the electron transfer ability within the electrode and lead to greatly enhanced specific capacity in both alkaline 5 M-KOH and neutral 0.5 M-K2 SO4 aqueous electrolytes (66.7 mA h g −1 and 47.5 mA h g −1 respectively for HCoO2 –PMIMBr and HCoO2 –EMIMBF4 compared to 18.1 mA h g −1 for bare HCoO2 in 5 M-KOH at 1 A g −1 ).